Dielectric Parameters of a Benzoate-Based Chiral Rod-Like Liquid Crystal - Ozerol, Esma Ahlatcioglu; Ocak, Hale (WILEY-V C H VERLAG GMBH, 2019)
In this study, the mesomorphic properties and dielectric parameters of a benzoate-based chiral rod-like liquid crystal 4-[4-(S)-3,7-Dimethyloctyloxybenzoyloxy]benzoic acid (DMOBB) were investigated. The rod-like liquid crystal with (S)-3,7-Dimethyloctyloxy chiral moiety exhibits enantiotropically chiral nematic (N*) phase and a wide-temperature chiral tilted smectic phase (SmC*) which is of a great interest due to broad application prospects. Dielectric Parameters of DMOBB chiral liquid crystal have been characterized by impedance spectroscopy in the frequency range between 1 Hz and 10 MHz at range of between 25 degrees C and 200 degrees C. In difference to the earlier works, this study provides a detailed investigation of the dielectric parameters of benzoate-based chiral rod-like liquid crystal.
Keywords: Chiral Mesophases; Dielectric; Liquid Crystals; Mesophases; Rod-like Liquid Crystal; Chemistry